Role of Indigenous Nitrogen-fixing Bacteria in Promoting Plant Growth on Post Tin Mining Soil - Widawati, Sri; Suliasih, (Makara Journal of Science, 2019)
Post tin mining soil is generally marginal with low pH, has poor nutrient content, and is thus unfavorable for plant growth, particularly for Sorghum bicolor, which is a nutrient-demanding plant. Indigenous bacteria are usually used in bioaugmentation to ameliorate environmental degradation due to their ability to adapt well. This research aimed to isolate indigenous nitrogen-fixing bacteria and evaluate its potential for promoting the growth of S. bicolor on post tin mining soil. Nitrogen-fixing bacteria were isolated from post tin mining soil by using specific media and identified by Bergey’s manual. Twenty five isolates were obtained, and eight of them (Azospirillum sp., Azospirillum lipoferum, Azotobacter chroococcum, A. paspalii, and Rhizobium sp.) were identified as nitrogen-fixing bacteria. A greenhouse experiment was conducted using factorial completely randomized design with three replications. The first factors were fertilizers, i.e., NPK; A. lipoferum CBT4 + NPK; A. lipoferum CBT4; and without fertilizer (control). The second factors were soil types, i.e., A (fertile soil from Cibinong), B (soil from Bangka Botanical Garden), C (soil from post tin mines two years after mining), and D (soil from active tin mining). Result showed that Azospirillum lipoferum CBT4 isolated from C (soil from post tin mines two years after mining) exhibited the highest IAA, Ca-P solubilizing ability, and PME-ase activity. This species survived up to a population of 107 CFU/gram soil in the three types of post tin mining soils and could be a potential plant-growth promoting rhizobacteria (PGPR) species for effectively improving the growth of S. bicolor plant on post tin-mining soil.